Treatment of hemangiomas in children using a Nd:YAG laser in conjunction with ice cooling of the epidermis: techniques and results - Charissis Georgios; Michailoudi Eleni; Gardikis Stefanos; Vlachakis Ioannis (BMC, 2003)
Abstract Background Hemangiomas are the most common type of congenital anomaly in childhood. Although many resolve spontaneously, intervention is required when their growth could damage vital adjacent structures. Various therapeutic approaches to childhood hemangiomas with different types of laser have been described previously. The objective of this study was to determine whether the cooling of the epidermis during irradiation of hemangiomas with a Nd:YAG laser prevents thermal damage and decreases the number of sessions required to treat these lesions. Methods Between 1993 and 2001, 110 patients aged 3 months to 4 years, with cutaneous hemangiomas were treated with a Nd:YAG laser. The lesion was cooled with ice prior to, during, and after the irradiation. During each session the laser beam passed through the pieces of ice. The laser power was between 35-45 W with a pulse length of 2-10 seconds. Results After 6 months of follow-up, from the first session of laser treatment, total resolution was obtained in 72 (65.5%) patients. A second or third session followed in 30 out of 38 patients in which, the initial results were good, moderate, or poor. The parents of the remaining eight children refused this second session and these patients excluded from the study Complications were seen in nine (8.8%) patients. One patient had postoperative bleeding which stopped spontaneously, while atrophic scars occurred in six (5.8%) patients, and hypertrophic scars in two (1.9%) patients. Conclusions Nd:YAG laser irradiation in conjunction with ice protection of the epidermis produces good cosmetic results for the treatment of cutaneous hemangiomas in children, and decreases the number of sessions for treatment of these lesions.